Early Predictors of Autism in Young Children Who Are Deaf or Hard of Hearing: Three Longitudinal Case Studies - Kellogg, Elizabeth Cameron; Thrasher, Amy; Yoshinaga-Itano, Christine (Seminars in Speech and Language, 2014)
Early assessment data (starting at 9 months) for three children who were deaf or hard of hearing and later diagnosed with autism spectrum disorder (ASD) were analyzed. The results from the MacArthur-Bates Communicative Development Inventories (CDI) Words and Gestures and the Child Development Inventory were used to develop three profiles of children who were deaf or hard of hearing and had ASD. One child lacked expected skills and language at ages 9 and 14 months. Another child lost skills and language after 17 months. The third child had results usually within or above the average range until 3 years of age. However, his age quotient decreased for MacArthur-Bates CDI: Words and Gestures Words Expressed and the Child Development Inventory: Social to significantly below the normal range. Although it can be difficult to diagnose the co-occurrence of ASD and deafness, there were early warning signs for these children.
Keywords: Autism; deaf; hard of hearing; children; developmental assessment; screening